Transport impacts of the Copenhagen Metro - Ildensborg-Hansen, Jane; Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
A large scale research project has followed the opening of the Copenhagen metro’s phase 1 and phase 2a where the focus was to analyse the changes in travel behaviour. A long list of transport impacts was identified and quantified in the project, all of them depended on a geographical location and the time the changes were measured relative to the before-metro situation. Due to the metro, we have experienced a general growth in public transport over the years after metro’s opening; an experience which is rather opposite of what we were used to. A major part of that increase is related to the newly generated traffic, i.e. induced traffic. Most of the new metro traffic happens in day periods out of the two peaks, especially in the evening, resulting in changes in the proportion of traffic in different day time periods, i.e. the peaks are less extreme in the after-metro situation. Finally, the metro has influenced changes in modal split, where the existing public transport modes, i.e. bus and S-train, lost large portions of their before-metro traffic to the metro. It was interesting to notice that in highly populated areas of Copenhagen, e.g. Frederiksberg, the metro had a large impact in shift from car to public transport.